Acceptability and feasibility of the Leapfrog computerized physician order entry evaluation tool for hospitals outside the United States. Issue 9 (September 2015) - Cho, Insook; Lee, Jae-Ho; Choi, Sun-Keun; Choi, Jin-Wook; Hwang, Hee; Bates, David W.
Highlights The Leapfrog evaluation tool was acceptable moderately and feasible sufficiently. The tool was beneficial to get the feedback about the safety categories. The tool can be more usable internationally if more scenarios and drugs are added. The safety levels of the four systems have many opportunities to improve over time.